The effects of materialism and ego depletion on intertemporal choice: An event-related potential study - Pei, Yingying; Yu, Junjian; Zhao, Lijun (Frontiers in Psychology, 2022)
Objective The study aims to promote human beings to make scientific and reasonable decisions for the long-term and beautiful future. Methods We designed two experiments to explore the influence of materialism and ego depletion from the perspective of behavioral decision-making and neural mechanism. Results In Experiment 1, there was asymmetry in intertemporal choice between gain and loss situations. In the gain situation, high materialism were more likely to choose the later and larger option (LL). However, in a loss situation, we found a reverse sign effect, and the proportion of subjects choosing sooner and smaller options (SS) increased. In Experiment 2, in the gain situation, after adding the low ego depletion task, there was a marginal significant difference between high and low materialism in the percentage of choosing LL options, F(1, 40) = 3.37, P = 0.07, η2 = 0.08; After adding the high ego depletion task, the percentage of choosing LL options was no difference, F(1, 40) = 1.42, P > 0.05. In the loss situation, whether in the high ego depletion task [F(1, 40) = 2.25, P > 0.05) or in the low ego depletion task [F(1, 40) = 1.44, P > 0.05), there was no difference between high and low materialism in the percentage of choosing LL options, and they both tended to choose SS options. The EEG study showed that in high materialism, there was a significant difference between the high and low ego depletion conditions, and the N1 amplitude induced under the low ego depletion condition was larger than that under the high ego depletion condition. However, there was no significant difference in N1 amplitude between the high and low ego depletion conditions in the low materialism. The amplitude of P2 evoked in the loss situation was larger than that in the gain situation. Conclusion In conclusion, Materialism dominated people’s intertemporal choices, and ego depletion affected the intertemporal choice to a certain extent by influencing the subjects’ thinking activities. The COVID-19 epidemic maybe affected intertemporal choice indirectly by acting on materialistic values and subjects’ emotions.